Nitrous oxide emission from different land use changes associated with oil palm plantation - Mat Akhir, Nurul Izzati; Mohd Kusin, Faradiella; Mohamat Yusuff, Ferdaus; Awang, Muhamad; Hamka, Farahana (American Research Institute for Policy Development, 2014)
The amount of nitrous oxide emission from syntheticfertilizer use in different scenarios of land use changes associated with oil palm plantation has been estimated.The plantations include two transformed land use estates (large and smallscale) and a logged-over forest converted into oil palm plantation. Field-determined data of soil N, P, K content at the oil palm plantations for oil palms varying in age were investigated (immature and mature palms). The amount of N-fertilizer applied ranged between 99.41-155.94 kg N/ha that results in19.11-22.35 kg N2O-N/ha. This corresponds with 1027.29-1430.31 kg CO2-eq/ha for the three different estates. The CO2-eq emission released per MJ crop produced was between 29.93- 35.02 g CO2-eq. Generally, the amount of N2O emissions were slightly higher for oil palms aged < 5 years (immature) for all categories of land use changes compared to more mature palms > 5 years.However, the highest CO2-eq emission was found from the logged-over forest for oil palms aged > 20 years. The variations in the resulting CO2-eq emission were found related with the carbon stock changes of the different land use transformation of the oil palm plantations.